Woman of interest : a memoir - O'Neill, Tracy (HarperOne, an imprint of HarperCollins Publishers, 2024)
"A National Book Foundation's 5 Under 35 honoree delivers her first nonfiction work: a compulsively readable, genre-bending story of finding her birth mother and learning the power of self-knowledge"--